The benefits and issues toward golden rice as genetic modified crop: a review / Muhammad Harith Rosman - Rosman, Muhammad Harith (Faculty of Plantation and Agrotechnology, 2019)
Golden Rice (GR) was developed to produce beta-carotene by genetic engineered (GE) method as the solution for vitamin A deficiency (VAD) problem. Beta-carotene act as pro-vitamin A which can convert to vitamin A in human body. Since GR is genetic modified (GM) crops, there are many issues raised among public include its effectiveness and impact show the reason of GR not commercialize for it uses and still under research until now. It be questioned by public, scientists and non-government organization because less information about this issue and lack of studies to show the future safety of golden rice regards to health and environment. The issues rise included gene contamination, potential unexpected effect with GR plant, risk to human health also compromising food security. GR also have their own potential benefits. It has been proven to have potential to assist in reducing VAD which become the public health problem especially in developing countries. The benefits of GR are shown on their effectiveness, safety, cost saving and maintain the original taste of the rice. The development and study of GR must be continued to answer all issues toward GR as well as improve and fixed the problem within GR.